Essential grammar in use with answers : - Murphy, Raymond (Cambridge University Press, 2014)
This set "is a grammar reference and practice book for elementary learners. Modelled on Raymond Murphy's highly successful intermediate level 'English grammar in use', it concentrates on areas of grammar normally taught at elementary level."